Studi Pemodelan Tipomorfologi Kampung Sunda: Studi Kasus Kampung Sehati Desa Nagrog Kecamatan Cicalengka Kabupaten Bandung - Sela Renika; Weishaguna; Saraswati (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. This study was preceded by the existence of phenomena that exist in the Sehati village, namely the interest in the Bandung district policy of applying 1000 Sundanese cultural preservation villages, the interest of exposing the uniqueness of the Kendan Tatar culture in the physical form of the Sundanese village and the existence of Sundanese village embryos in the Nagrog village but not yet conceptualized according to the theme of cultural preservation. So this study focuses on the question "How is the typomorphological model of a representative Sundanese village?". The purpose of this study is "Creating a model of a healthy village that represents the cosmology of Sundanese cultural space". This study uses a qualitative approach and a hermenitic approach with comparative analysis methods being solved including the variables of zoning, Sundanese land use, Sundanese village physical elements and Sundanese village cultural activities. Analyzed with the criteria of the tri tangtu concept, the opinion of rina priyani, nurhamsah and the ancient manuscript, namely siksakandang karesian which divides the land into weak malaning and weak nir malaning. The conclusion of this study is that the division of zones includes Buana nyuncung, Buana Panca Tengah and Buana Larang. The land use for Sunda includes Cultivation Areas and Conservation Areas. Furthermore, the application of the model in the physical elements of the Sundanese village includes the alun-alun, imah stage model, bale nyuncung, bale motekar, bale puhun, buruan, leuit, saung lisung, gardens, cages and balloons with representations of educational culture with modern and Islamic values. Abstrak. Studi ini didahului karena adanya fenomena yang ada dikampung sehati yaitu adanya kepentingan kebijakan kabupaten bandung terapkan 1000 kampung pelestarian budaya sunda, kepentingan mengekspos kekhasan budaya tatar kendan dalam wujud fisik kampung sunda dan sudah adanya embrio kampung sunda di desa nagrog namun belum terkonsep sesuai tema pelestarian budaya. Sehingga studi ini terfokus pada pertanyaan “Bagaimana model tipomorfologi kampung sunda yang representatif?”. Tujuan studi ini yaitu “Membuat model kampung sehati yang merepresentasikan kosmologi ruang budaya sunda”. Studi ini menggunakan metode pendekatan kualitatif dan pendekatan hermenitik dengan dipecahkan metode analisis komparasi meliputi variabel pembagian zona, peruntukan lahan sunda, elemen fisik kampung sunda dan aktivitas budaya kampung sunda. Di analisis dengan kriteria konsep tri tangtu, pendapat rina priyani, nurhamsah serta naskah kuno yaitu siksakandang karesian yang membagi lahan menjadi malaning lemah dan nir malaning lemah. Kesimpulan dari studi ini yaitu pada pembagian zona meliputi buana nyuncung, buana panca tengah dan buana larang. Untuk peruntukan lahan sunda meliputi Kawasan budidaya dan Kawasan konservasi. Selanjutnya penerapan model dalam elemen fisik kampung sunda meliputi model alun-alun, imah panggung, bale nyuncung, bale motekar, bale puhun, buruan, leuit, saung lisung, kebon, kandang dan balong dengan representasi budaya edukasi yang bernilai modern dan islami.